Haematocrit, hypertension and smoking in patients with transient ischaemic attacks and in age and sex matched controls. Issue 6 (June 1982) - Harrison, M J; Pollock, S; Thomas, D; Marshall, J
Abstract : The blood pressure, smoking habit and haemotocrit of 154 patients with transient ischaemic attacks and 191 age-and sex-matched neurological controls were studied. Regression analysis revealed that the haematocrit value was related to both systolic and diastolic blood pressure, and to smoking. Smoking elevated the haematocrit by 1.9 +/- 0.59 in males and by 2.18 +/- 0.68 in females. When these associations were allowed for there was still evidence of a higher haematocrit in patients with transient ischaemic attacks (plus 1.44 +/- 0.56 in males and 0.75 +/- 0.75 in females p less than 0.02). The role of an elevated haematocrit in the pathogenesis of cerebrovascular disease and its management are briefly discussed.